Palm Oil Modulates Haematological Profile and ATPase Activities of Wistar Rats - Igbonomi, Israel Paul; Asiriuwa, Nathaniel; Ejiro, Dowe; Eznogua, Vivien; Osahon, Abu; Osaretin, Osemwenkhae (FUDMA Journal of Sciences, 2026)
Palm oil is widely consumed globally, yet its effects on health remains a topic of debate. In this study, the effect of palm oil on haematological indices and ATPase activities in Wistar rats was assessed. Thirty-six (36) adult rats were divided into six groups of six rats each made of normal rats (group 1). Group II served as experimental control and was given fresh palm oil of 0.4 % FFA. Groups III-VI were given palm oil that has been stored for sixteen months of varied FFA levels (4.8, 8.4, 21.9, and 42.7 %) respectively. The rats were administered a dosage of 480 mg/kg body weight of CPO orally for four weeks. Haematological parameters, including red blood cell count, packed cell volume, haemoglobin, platelets, white blood cell and differential counts were measured using standard haematology analyzer. ATPase activities were also assessed to determine metabolic and enzymatic activities using standard methods. The results indicate that significant alterations were observed in the haematological profile of stored palm oil-fed rats, including changes in haemoglobin and erythrocyte counts. ATPase activity was also modulated, indicating mild disruptions in cellular energy metabolism. The study suggests that free fatty acids levels in palm oil determine its effects on haematological and ATPase activity in Wistar rats.